The Role of Endowment in Growing and Developing Scientific Research in the Universities of Gulf Cooperation Council States - Alanzi, Manhl E. (Humanities Journal of University of Zakho, 2013)
This paper deals with role of Endowment as an Islamic institution that serves the society in its scientific education 'and Intellectual aspects. The first part of this paper investigates the Islamic Endowment system with its sigmficance, legitemation, Linguistic terminological sense then its corner stones' parts and its positive motivations are also studied. The historical role of Endowment in the educational field through Islamic history are dealt in this part. The second pant sheds lights on the role of Endowment in society in Its intellectual, educational, and scientific aspects. It starts with the contributions of scientific research in the Universities of gulf cooperation council States historically and the developing stages of University educational system and the continuation of process in the universities of GCC in its message and strategies. This paper includes an explanation of experiences of modern Gulf countries in the administration of Endowment in Vestment as an example. The study comes cross the administrations of Endowment financial investments and the principles of Endowment fund of social and scientific development as an example of what the kwaite state has paid a great attention in the field of Intellectual, educational, and cultural development. Finally, The study includes a summary, conclusion findings, suggestion and recommendations which participate in developing the scientific research in the universities of Gulf Cooperation Council states.